PENGARUH PENEMPATAN KARYAWAN DAN KOMPENSASI TERHADAP KOMPETENSI KARYAWAN PADA UNIT KONVEKSI PRIMKOPAD BEKANGDAM III / SLW - Irawan, Andri (Jurnal Manajemen dan Keuangan, 2010)
The purpose of this study was to determine the extent of the impact of staffing and compensation of employees competence and their implications for methods of personnel working in the unit